Evolution of left ventricular function among subjects with ST-elevation myocardial infarction after percutaneous coronary intervention - Pahlm, Ulrika; Ostenfeld, Ellen; Seemann, Felicia; Engblom, Henrik; Erlinge, David; Heiberg, Einar; Arheden, Håkan; Carlsson, Marcus (BMC cardiovascular disorders, 2020)
Background Atrioventricular plane displacement (AVPD) reflects longitudinal left ventricular (LV) systolic function, and wall thickening (WT) regional radial LV function. The temporal evolution of these measures after STEMI with CMR has not been evaluated. We aimed to investigate how AVPD and WT are affected globally and regionally from the sub-acute to the chronic phase after ST-elevation myocardial infarction (STEMI). Methods Healthy volunteers without cardiovascular disease and medication (controls, n = 20) and patients from the CHILL-MI study ( NCT01379261 ) prospectively underwent magnetic resonance imaging (MRI) 2–6 days and 6 months after STEMI ( n = 77). CHILL-MI randomized STEMI-patients to cooling therapy initiated before reperfusion or standard of care. AVPD was measured at six points in three long axis cine images and wall thickening in short axis cine images. Infarction was quantified using late gadolinium enhancement (LGE) and used to define infarct and remote segments. Results There were no difference in AVPD either at acute or chronic phase ( p = 0.90 and p = 0.40) or WT ( p = 0.85 and p = 0.99) between patients randomized to cooling therapy and standard of care. Therefore, the results are presented for the pooled cohort. Global AVPD was decreased in both the sub-acute (12 ± 2 mm, p < 0.001) and the chronic phase (13 ± 2 mm, p < 0.001) compared to controls (15 ± 2 mm) with a partial recovery of AVPD (p < 0.001) in the chronic phase. Patients with left anterior descending (LAD) and right coronary artery (RCA) infarcts had decreased AVPD in the chronic phase in both infarcted and remote segments. Mean WT was decreased in patients with LAD infarction both in the sub-acute and the chronic phase in both infarcted and remote segments. The decrease in WT in patients with RCA and left circumflex (LCx) infarcts was more affected in the infarcted segments, especially in the chronic phase. Conclusion AVPD was a global rather than regional marker of cardiac function in this STEMI study and this may explain the prognostic importance of local measurements of mitral annular plane systolic excursion (MAPSE). The decrease in WT in remote myocardium even in the chronic phase needs to be taken into consideration when combining functional measurements with infarct quantification for diagnosis of post-ischemic stunning and hibernation.